2007
DOI: 10.1152/ajpcell.00286.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular recruitment and cytokine generation in a rat model of allergic lung inflammation are differentially modulated by progesterone and estradiol

Abstract: We evaluated the role of estradiol and progesterone in allergic lung inflammation. Rats were ovariectomized (Ovx) and, 7 days later, were sensitized with ovalbumin (OA) and challenged after 2 wk with inhaled OA; experiments were performed 1 day thereafter. Ovx-allergic rats showed reduced cell recruitment into the bronchoalveolar lavage (BAL) fluid relative to sham-Ovx allergic rats, as was observed in intact allergic rats treated with ICI-182,780. Estradiol increased the number of cells in the BAL of Ovx-alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 55 publications
3
57
1
Order By: Relevance
“…However, the role of estrogen in allergic inflammation is controversial with studies such as those by Dimitropoulou et al [6] showing that implantation of estradiol pellets in OVX mice before sensitisation reduced airway inflammation. The use of models employing OVX to study the role of estrogen in allergic inflammation is complicated because ovarian products other than estrogen may influence the observed effects [7]. Indeed, a recent study suggested an important consideration when analysing the role of sex hormones in allergic disease is not the levels of circulating estrogen per se, but the estrogen/progesterone ratio [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of estrogen in allergic inflammation is controversial with studies such as those by Dimitropoulou et al [6] showing that implantation of estradiol pellets in OVX mice before sensitisation reduced airway inflammation. The use of models employing OVX to study the role of estrogen in allergic inflammation is complicated because ovarian products other than estrogen may influence the observed effects [7]. Indeed, a recent study suggested an important consideration when analysing the role of sex hormones in allergic disease is not the levels of circulating estrogen per se, but the estrogen/progesterone ratio [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of models employing OVX to study the role of estrogen in allergic inflammation is complicated because ovarian products other than estrogen may influence the observed effects [7]. Indeed, a recent study suggested an important consideration when analysing the role of sex hormones in allergic disease is not the levels of circulating estrogen per se, but the estrogen/progesterone ratio [7]. In congruence with this concept, estradiol supplementation of OVX mice does not fully compensate the anti-inflammatory effects of OVX in allergic airway disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Interleukin (IL) like IL-10, IL1-β, and Tumor Necrosis Factor (TNF)-α will increase by the effect of progesterone. 12 Female hormones also have an impact on T helper cell. 11 Females have a better humoral immunity than males, who demonstrate a better cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is an early-response, pro-inflammatory cytokine that has been shown to be integral in the pathogenesis of other lung injury models that are neutrophil-mediated [17][18][19][20] . TNF-α leads to activation of leukocytes and induces the expression of endothelial adhesion molecules that play a major role in the leukocyte-endothelial interactions that lead to neutrophil migration into the alveoli 21 .…”
Section: Discussionmentioning
confidence: 99%